The Impact of FDI on Domestic Firm Innovation : Evidence from Foreign Investment Deregulation in China - Liu, Yan; Wang, Xuan (World Bank, Washington, DC, 2021)
This paper studies the impact of foreign direct investment on domestic firms’ innovation in China. It provides causal evidence by exploiting China’s foreign direct investment deregulation in 2002 and employs a difference-in-difference estimation strategy. Using a matched firm-patent data set from 1998 to 2007, the results show that the quantity and quality of domestic firms’ innovation benefit from foreign direct investment. Moreover, the paper emphasizes the importance of knowledge spillover from foreign direct investment in similar technology domains. The analysis examines the role of horizontal foreign direct investment and foreign direct investment in technologically close industries—industries that share similar technology domains. The findings show that foreign direct investment in technologically close industries generates much bigger positive spillovers than horizontal foreign direct investment. The paper also shows that knowledge spillover from foreign direct investment in similar technology domains is not driven by input-out linkages. Moreover, the spillover effect is stronger in cities with higher human capital stock and firms with higher absorptive capacity.